2012
DOI: 10.1086/668433
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vancomycin Minimum Inhibitory Concentration on Mortality among Critically Ill Patients witn Methicillin-Resistant Staphylococcus aureus Bacteremia

Abstract: We retrospectively evaluated 99 intensive care unit patients with methicillin-resistant Staphylococcus aureus bacteremia to determine whether having a vancomycin minimum inhibitory concentration (MIC) of 2 mg/L affected mortality. This MIC was found in 5.1% of patients and was associated with the probability of death (adjusted odds ratio, 13.9 [95% confidence interval, 1.1-171.2]) independent of other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…After reviewing the full texts, we excluded other studies according to the eligibility criteria. Twenty studies (4,5,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) were included in the final analysis. The process of article selection is shown in Figure 1.…”
Section: Results Of Study Inclusionmentioning
confidence: 99%
“…After reviewing the full texts, we excluded other studies according to the eligibility criteria. Twenty studies (4,5,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) were included in the final analysis. The process of article selection is shown in Figure 1.…”
Section: Results Of Study Inclusionmentioning
confidence: 99%
“…The failure of vancomycin treatment in certain S. aureus infections which, based on standard susceptibility testing, should have been susceptible to the bactericidal effects of this antimicrobial (i.e., VSSA strains) has been well documented ( 31 40 ). MIC elevations comparable to those induced by colistin exposure have been associated with increased mortality ( 32 , 35 , 37 , 41 ). As removal of colistin restored vancomycin sensitivity to the precolistin level, our results raise the prospect that an infecting S. aureus strain isolated from a patient receiving colistin may be reported as being highly sensitive ( 42 ), whereas the actual susceptibility of bacteria present in that patient may be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…With increased use, the susceptibility of MRSA to vancomycin has been shifting toward higher MICs, termed MIC creep, which has been associated with increased mortality. Woods and colleagues 43 reported that the prevalence of MRSA with an MIC of 2 mg/L in their patients in ICUs with bacteremia was 5.1%. They noted an escalation of mortality as MIC increased, up to 80% when reaching an MIC of 2 mg/L.…”
Section: Gram-positive Infectionsmentioning
confidence: 99%